Length-Weight Relationship And Condition Factor Of Indian Major Carp (Labeo Rohita Ham., 1822) From Southern Rajasthan, India (Applied Biological Research, 2013)
The length-weight relationships (LWR) of commercially important Indian  major carp (Labeo rohita Ham. 1822) from three water bodies of southern  Rajasthan viz., Mahi Bajaj Sagar (MBS), Surawania Dam (SD) and Aasana  Pond (AP) were studied. The important parameters on LWR were calculated  for Rohu in these selected water bodies and the correlation coefficient ‘r’ was  significant with observed values of 0.99, 0.99 and 0.97 for MBS, SD and AP,  respectively for pooled data. However, these values ranged from 0.74-0.88 in  MBS, 0.46-0.95 in SD and 0.75-0.95 in AP in different length groups of Rohu. In  LWR (W = aLb) values of exponent ‘b’ were observed to be 2.98, 2.97 and 3.14  in MBS, SD and AP in the pooled data. The values of ‘K’ ranged from 2.01-2.21  in MBS, 2.05-2.34 in SD and 2.05-2.29 in AP in different length groups. Such  values for pooled data were 2.02, 2.05 and 2.38 for MBS, SD and AP fishes  respectively which shows that comparatively AP is more conducive water body  for the fish growth. The values of ‘Kn’ ranged from 0.99-1.00 which depicted  condition of fish in these water bodies. These observed parameters were  useful to evaluate the well being of Rohu population in the water bodies and  provided useful information on fish biology for scientific management of  fisheries.
Keywords: Growth; Indian major carps; length-weight relationships; Rohu